Effect of epigenetic inhibitors on lung fibroblast phenotype change in idiopathic pulmonary fibrosis - Pasini, Alice; Brand, Oliver J.; Jenkins, Gisli; Knox, Alan J.; Pang, Linhua (BMJ Publishing Group, 2016)
Introduction and objectives: Idiopathic Pulmonary Fibrosis (IFP) is a fatal interstitial lung disease with unknown aetiology. Lung myofibroblasts (activated fibrobalsts) are the major effector cells in the pathogenesis of IPF. Transforming growth factor-β (TGF-β1) is a potent activator of fibroblasts. Lack of effective treatment options necessitates novel therapeutic approaches. Epigenetic drugs, by inhibiting chromatin modifying enzymes involved in gene expression control, represent promising agents capable of modulating the cellular phenotype.